Systematic review of the therapeutic potential of the hiccup-nut tree, Combretum bracteosum (Hochst.) Brandis. - Maroyi, Alfred (Student's Journal of Health Research Africa, 2025)
Background Combretum bracteosum (Hochst.) Brandis is a free-standing and many-stemmed shrub or a small tree used in traditional medicine throughout its distributional range. The current study aimed at reviewing the medicinal uses and ethnopharmacological properties of C. bracteosum. Methods A systematic review of scientific literature on the therapeutic potential of C. bracteosum was conducted following the Preferred Reporting Items for systematic reviews and meta-analyses (PRISMA). The literature search was conducted using databases PubMed, Web of Science, ScienceDirect, Google Scholar, SpringerLink, Scopus, and SciELO, as well as pre-electronic literature sources such as book chapters, books, and other scientific publications obtained from the university library. Results Results from this systematic review revealed that C. bracteosum is used as traditional medicine against backache, convulsions, earache, epilepsy, fever, headache, hiccough, menstrual pains, rheumatism, toothache, and scalp infection in children. The phytochemical assessment of C. bracteosum showed that the species contains proanthocyanidin, gallotannin, anthocyanin, flavonol, flavonoids, phenolics, saponins, steroids, cardiac glycosides, and tannins. The crude extracts of C. bracteosum demonstrated antibacterial, antimycobacterial, antifungal, anti-inflammatory, antioxidant, and GABAA-benzodiazepine receptor binding activities. Conclusion This traditional ecological knowledge about C. bracteosum accumulated from the past to the present is extremely important and of great value in the assessment of the therapeutic potential and ethnopharmacological value of the species. Recommendations Future research on C. bracteosum should focus on detailed phytochemical, pharmacological, and toxicological evaluations of the crude extracts as well as phytochemical compounds isolated from the species.